Synthesis of mangiferin derivatives, complexes, and carriers as potential therapeutic candidates for cancer treatment: an update - Melo-Betances, Elianny; Rodríguez-Bautista, Crismery C.; Núñez-Sellés, Alberto J. (Frontiers in Pharmacology, 2025)
Mangiferin (MF), a xanthonoid polyphenol, its derivatives, coordination and inclusion complexes, and carriers have demonstrated notable antitumor activity in vitro and in vivo. However, their clinical application remains limited due to MF’s poor water solubility and low systemic bioavailability. This review critically summarizes advances in the synthesis of MF derivatives and formulation strategies, such as metal complexes, cyclodextrin inclusion systems, and nanocarriers, developed over the past decade to enhance MF’s bioavailability and therapeutic efficacy. Promising results include glycosylated derivatives, MF-Se (IV) metal complexes, and β-cyclodextrin complexes, each contributing to improved solubility and cytotoxicity profiles. Continued research is essential to bridge the gap between experimental success and its clinical implementation in cancer therapy.